Strategies for Improving the Educational Capacity of Professional Skills Teachers in Vocational Education - ZHENG Yuxuan (Journal of Exploration of Vocational Education, 2025)
Abstract：The educational capacity of vocational education teachers is a key factor in enhancing teaching quality and students' professional competence. Existing research and policy documents indicate that the training of dual-skilled teachers, the optimization of school-enterprise cooperation models, and the establishment of lifelong learning mechanisms are the main pathways for enhancing teachers' educational capacity. However, there is still controversy regarding the definition of capability components, the depth of school-enterprise cooperation, and the effectiveness of training models. To address these issues, this study primarily employs literature research and case analysis to systematically review recent theoretical and practical achievements in improving vocational education teachers' educational capacity. Through analysis of typical school-enterprise cooperation cases, it explores effective strategies for improving teachers’ educational capacity. The study finds that the cultivation of dual-skilled teachers is a core approach to improving teachers' educational capacity. The key to success lies in deep school-enterprise cooperation and the integration of practical skills with teaching abilities. The lifelong learning mechanism needs to rely on information platforms and diversified training formats to enhance the flexibility and efficiency of teachers’ continuous learning. Additionally, the enthusiasm of enterprises to participate and unified cooperation standards are key factors influencing the success of cooperation. This study further proposes strategies to establish a long-term mechanism for cultivating dual-skilled teachers, improve the teacher educational capacity evaluation system, and innovate training and lifelong learning support systems, providing theoretical support and practical references for the enhancement of vocational education teachers’ capabilities. Future research is recommended to focus on the priority order of capability components, regional differences, and the application of digital technologies.